TNF-α and IL-1 in migraine, current knowledge and future perspectives: literature review - Putri Rossyana Dewi; I Made Oka Adnyana; I Putu Eka Widyadharma (Department of Anatomy, Medical Faculty, Universitas Udayana, Bali-Indonesia, 2020)
Background: Migraine is closely related to physical and biopsychosocial problems on human. The increasing number of migraine cases can affect the quality of life and increasing financial burden. Aim: The study aims to simply review the presentation of TNF- α and IL-1 in migraine mechanisms as well as the perspective of their future agenda. Review: The characteristics of migraine symptoms include unilateral and pulsating headaches precede by fatigue, irritability, decrease of concentration, and daytime sleepiness. Vascular and neurovascular theory are previous theory about the pathophysiology of migraine. Recent knowledge state that cortical spreading depression is the underlying mechanism of the aura and migraine. Other literatures showed that neurogenic inflammation also play a role in migraine particularly mast cells. Mast cells degranulate pro-inflammatory cytokines including TNF-α and IL-1, chemokines, and other substances. The involvement of TNF-α and IL-1 in migraine will be discussed in this review.